(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2019)
This essay, composed for a first-year writing seminar on war and human rights, examines the 1994 Rwandan ethnic cleansing. The author argues that Hutu extremists systematically disintegrated Tutsi communities by employing rape as a weapon physically directed against women with the expressed intention of unraveling the fabric of entire Tutsi family networks which placed women and mothers at the heart of their kinship groups. For additional context, listen to the author’s reflection on the piece below.